2003
DOI: 10.3998/ark.5550190.0003.b20
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of pyrazole-4-carbohydrazide derivatives of pharmaceutical interest

Abstract: New 1-phenyl-or 1-methyl-5-benzamidopyrazole-4-carbohydrazide derivatives were prepared in 70-90% yields from 1-methyl-or 1-phenyl-6-phenylpyrazolo[3,4-d]1,3-oxazin-4(1H)-one derivatives and hydrazine hydrate. Small quantities of the isomeric 5-aminopyrazole-4-(Nbenzoyl)hydrazides were detected in some reaction mixtures, proving that intramolecular benzoyl migration can take place in the 5-benzamidopyrazole-4-carbohydrazide molecule. The direct formation of pyrazole-4-carbohydrazides from 5-benzamidopyrazole-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Sigma-Aldrich provided all of the compounds, which were utilized without additional purification. Compounds 2 27 , 4 32 and 6 39 were synthesized according to the previously reported procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sigma-Aldrich provided all of the compounds, which were utilized without additional purification. Compounds 2 27 , 4 32 and 6 39 were synthesized according to the previously reported procedures.…”
Section: Methodsmentioning
confidence: 99%
“…)ethylidene]hydrazine (6) 39 . In ethanol, 1-(Benzofuran-2-yl)ethan-1-one (2) (1.6 g, 10 mmol) was refluxed for 2 h with hydrazine hydrate 99% (0.5 g, 0.5 ml, 10 mmol) The white precipitate was filtered before being crystallized from ethanol.…”
Section: Preparation Of (E)-[1-(benzofuran-2-ylmentioning
confidence: 99%
“…In 2015, Venkatesan et al [24] reported the reaction of the pyrazole was obtained by reacting 41 with triethyl orthoformate [25] (Scheme 13). Raffa et al [26] reported that condensation of 5-amino-1H-…”
Section: From Amino Pyrazole 4-carboxamide Derivativesmentioning
confidence: 99%
“…There are several approaches reported in the synthesis of pyrazolo [3,4-d]pyrimidines, for instance: reaction of 5-amino-pyrazole-4-carbohydrazides with formamide and hydrazine hydrate under microwave irradiation (Todorovic et al 2011), or with urea anddecaline (Ghorab et al 2010) or with benzoyl chloride derivatives and triethylorthoformate (Daidone et al 2002). There are reports on the reaction of ethyl 5-amino-1H-pyrazole-4-carboxylates with hydrazine hydrate and triethylorthoformate (Ghorab et al 2010) and also with formamide or benzoyl isothiocyanate (Carraro et al 2006) as well as reaction of 4-hydrazinylpyrimidine derivatives with isocyanates (Bhuyan et al 2002).…”
Section: Introductionmentioning
confidence: 99%